Perbandingan Pendapatan Usahatani Cabai Rawit dengan Menggunakan Pupuk Anorganik dan Pupuk Campuran(Organik, dan Anorganik) (Studi Kasus di Subak Kudungan, Desa Bontihing, Kecamatan Kubutambahan, Kabupaten Buleleng) - RIFKI ARDIAN; WAYAN SUDARTA; I KETUT RANTAU (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
The Comparison of Hot Chili Farming Incomes by Using Organic Fertilizer and Mixture Fertilizer (Organic, and Inorganic)(Case Study In Subak Kudungan, Bontihing Village, Kubutambahan Distric,Buleleng Regency)The problem faced by famers of hot chili is obstacle the cultivation which done from the less production result of achieve national potential target of 10 to 20 tonnes/ha and to overcome obstacles especially in plants cultivation which done by applying a low-tech chemical inputs and cultivation technology of conservation which is implemented in integrated crop processing hot chili by applying organic fertilizer. Therefore this research aims to know the comparison of hot chili farming incomes by using organic fertilizer and mixture fertilizer. This research was conducted from August until September 2016 in Subak Kudungan Bontihing village Kubutambahan distric Buleleng regency. The data were analyzed by income analysis, R/C ratio analysis and Uji-t analysis. The results showed that hot chili farming incomes in one season per hectare using inorganic fertilizer is loweer than using a mixture fertilizer, use inorganic fertilizer Rp 21. 586.846,00 and use mixture fertilizer Rp 26.489.791,00. R/C ratio hot chili farming using organic fertilizer which is 2,09 higher than using mixture fertilizer 2,03. The result of Uji-t analysis showed hot chili farming incomes using inorganic fertilizer and mixture fertilizer was not significantly different at the level 5%.